Race, Gender, and the History of Early Analytic Philosophy - LaVine, Matt (Lexington Books, 2020)
Matt LaVine argues that there is more potential in bringing the history of early analytic philosophy and critical theories of race and gender together than has been traditionally recognized. In particular, he explores the changes associated with a shift from revolutionary aspects of early analytic philosophy.